(untitled) (Jurnal Pendidikan Fisika, 2026)
Wave concepts in physics are inherently abstract and often lead to misconceptions, especially when virtual laboratory activities are implemented without structured classroom management and guided reflection. Additionally, virtual science learning is frequently focused mainly on cognitive outcomes, while character development, particularly integrity in scientific practice, receives less systematic attention. This study addressed this gap by developing and evaluating a classroom management guide for Virtual Science Labs (PhET Simulations) based on the Experiential Learning Cycle (ELC) and integrated with prophetic values to enhance university students’ understanding of wave phenomena while fostering character development. Using a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the study involved 14 fifth-semester students from the Physics Education Study Program at Universitas Muhammadiyah Prof. Dr. HAMKA in the 2024–2025 academic year. Data were collected through expert validation sheets, wave conceptual understanding tests (pre-test and post-test), and prophetic character observation sheets. Expert validation indicated that the guide was highly feasible, with a mean score of 3.67 (87.5%) for content validation and 3.33 (83.3%) for media validation. Effectiveness results showed significant improvement in conceptual understanding, with scores increasing from 42.50 (pre-test) to 85.40 (post-test) and an N-gain of 0.75 (high category). Observations also suggested successful enactment of prophetic values during PhET-based practicums, particularly Sidiq (90%) and Amanah (85%), reflected in honest data recording and responsible task completion. The novelty of this study lies in the systematic integration of ELC-based classroom management, interactive PhET visualization, and the operationalization of prophetic values within a single instructional product. Overall, the developed model is feasible and effective for supporting both conceptual learning and character development focused on integrity in wave instruction, offering a comprehensive contribution to higher-education physics education.